Canada. Significant Achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Canada during 2020 are identified, with respect to the needs and interests of the country, in favor of rural communities, food security, gender equity and trade. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized.